PEMBUATAN PETA GEOSPASIAL MELALUI PEMETAAN UDARA PADA KELURAHAN BATU BERSURAT, KECAMATAN XIII KOTO KAMPAR, KABUPATEN KAMPAR, PROVINSI RIAU - Feblil Huda; Kaspul Anuar; Syafri Syafri; Anita Susilawati (Universitas Lancang Kuning, 2019)
One of the most commonly used geospatial mapping methods is photogrammetry (aerial mapping). Photogrammetry is a method of mapping objects on the surface of the earth by using aerial photography as a medium. The aerial mapping process is carried out through cameras installed on Unmanned Aerial Vehicle (UAV). From the aerial photography, object interpretation and geometry measurements will be carried out to produce line maps, digital maps and photo maps. In general, photogrammetry is a mapping technology by utilizing aerial photography to be processed into a geo-spatial information system. Batu Bersurat Village is one of the villages located in Subdistrict XIII Koto Kampar, Kampar Regency, which did not have a geospatial information map. Community service team from the Mechanical Engineering Department of the University of Riau had a plan to carry out community service activities in Batu Besurat Village in the form of making geospatial information maps through aerial mapping. This aerial mapping activity was carried out by utilizing UAV with the type of fixed wing. In its implementation, the community service activities were planned to involve Mechanical Engineering students, university students of the University of Riau, village officials and the local community. It is expected that with this community service program, the geospatial information system map made by Batu Bersurat Village can be used in village spatial planning for agricultural land, residential land and validation of village boundaries.